2017
DOI: 10.1096/fj.201700237rr
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cells promote triple‐negative breast cancer cell metastasis via PAI‐1 and CCL5 signaling

Abstract: Endothelial cells (ECs) in the tumor microenvironment have been reported to play a more active role in solid tumor growth and metastatic dissemination than simply providing the physical structure to form conduits for blood flow; however, the involvement of ECs in the process of triple-negative breast cancer (TNBC) metastasis has not been addressed. Here, we demonstrate that ECs-when mixed with TNBC cells-could increase TNBC cell metastatic potency. After treatment with TGF-β to induce endothelial-mesenchymal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 41 publications
(50 reference statements)
3
58
0
Order By: Relevance
“…To explore whether certain factors conferred to resistance of saracatinib, we evaluated the mRNA expression profile between parental cell line SKBR-3 and resistant cell line SKBR-3/SI. On the basis of our laboratory's previous study results, which hint that PAI-1 accelerates malignancy in breast cancer and is a prominent factor during tumor development and progression, 17 we further found that mRNA expression of PAI-1 was increased in the resistant cell line. Interestingly, gene ontology analysis of genes with over 2-fold change between SKBR-3/SI and SKBR-3 revealed an enrichment of factors involved in positive regulation of monocyte chemotaxis, which also was reported to interact with PAI-1 to enhance disease progression of breast cancer in our early data (Figure 2A).…”
Section: Pai-1 Was Upregulated In Saracatinib-resistant Cell Linesupporting
confidence: 58%
See 4 more Smart Citations
“…To explore whether certain factors conferred to resistance of saracatinib, we evaluated the mRNA expression profile between parental cell line SKBR-3 and resistant cell line SKBR-3/SI. On the basis of our laboratory's previous study results, which hint that PAI-1 accelerates malignancy in breast cancer and is a prominent factor during tumor development and progression, 17 we further found that mRNA expression of PAI-1 was increased in the resistant cell line. Interestingly, gene ontology analysis of genes with over 2-fold change between SKBR-3/SI and SKBR-3 revealed an enrichment of factors involved in positive regulation of monocyte chemotaxis, which also was reported to interact with PAI-1 to enhance disease progression of breast cancer in our early data (Figure 2A).…”
Section: Pai-1 Was Upregulated In Saracatinib-resistant Cell Linesupporting
confidence: 58%
“…On the basis of our laboratory's previous study results, which hint that PAI‐1 accelerates malignancy in breast cancer and is a prominent factor during tumor development and progression, we further found that mRNA expression of PAI‐1 was increased in the resistant cell line. Interestingly, gene ontology analysis of genes with over 2‐fold change between SKBR‐3/SI and SKBR‐3 revealed an enrichment of factors involved in positive regulation of monocyte chemotaxis, which also was reported to interact with PAI‐1 to enhance disease progression of breast cancer in our early data (Figure A) . Hence, we chose PAI‐1 for further research and confirmed that expression of PAI‐1 in SKBR‐3/SI was relatively higher in mRNA and protein levels than in SKBR‐3 (Figure B,C).…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations